Analysis of Priority-Based Communication Feature Using UI/UX Design Thinking Model: A Case Study of WhatsApp - Nurul Badriah; Sony Veri Shandy; Fajar Muttaqi; Moh Alfaujianto (Universitas Utpadaka Swastika, 2026)
The rapid growth of instant messaging applications has significantly transformed the way individuals communicate in both personal and professional contexts. However, the increasing volume of incoming messages often leads to information overload, making it difficult for users to distinguish between important and less relevant conversations. This study aims to design and implement a priority-based communication feature using a Design Thinking approach, with WhatsApp as a case study. Unlike conventional chronological message ordering, the proposed system allows users to manually define priority contacts through a “High Priority Mode” feature, enabling important conversations to be automatically positioned at the top of the chat list. In addition, the system introduces visual differentiation in notifications to highlight messages from priority contacts. A prototype interface is developed to support intuitive configuration and improve usability. The results indicate that the proposed feature enhances message visibility, reduces the risk of overlooking important communications, and improves overall user efficiency. This study demonstrates that a user-centered, rule-based approach can provide a practical and effective solution for managing communication priorities in messaging applications.